Facility-based active management of the third stage of labour: assessment of quality in six countries in sub-Saharan Africa - Linda Bartlett; David Cantor; Pamela Lynam; Gurpreet Kaur; Barbara Rawlins; Jim Ricca; Vandana Tripathi; Heather E Rosen (The World Health Organization, 2015)
Abstract Objective To assess the quality of facility-based active management of the third stage of labour in Ethiopia, Kenya, Madagascar, Mozambique, Rwanda and the United Republic of Tanzania. Methods Between 2009 and 2012, using a cross-sectional design, 2317 women in 390 health facilities were directly observed during the third stage of labour. Observers recorded the use of uterotonic medicines, controlled cord traction and uterine massage. Facility infrastructure and supplies needed for active management were audited and relevant guidelines reviewed. Findings Most (94%; 2173) of the women observed were given oxytocin (2043) or another uterotonic (130). The frequencies of controlled cord traction and uterine massage and the timing of uterotonic administration showed considerable between-country variation. Of the women given a uterotonic, 1640 (76%) received it within three minutes of the birth. Uterotonics and related supplies were generally available onsite. Although all of the study countries had national policies and/or guidelines that supported the active management of the third stage of labour, the presence of guidelines in facilities varied across countries and only 377 (36%) of 1037 investigated providers had received relevant training in the previous three years. Conclusion In the study countries, quality and coverage of the active management of the third stage of labour were high. However, to improve active management, there needs to be more research on optimizing the timing of uterotonic administration. Training on the use of new clinical guidelines and implementation research on the best methods to update such training are also needed.